Consumer segmentation by online information search behavior in Yinchuan, China - Beiyu, Zhu; Hashim, Ahmad Hariza; Osman, Syuhaily; Abu Bakar, Elistina (Asian Online Journals, 2016)
Consumers in China increasingly rely on the Internet for product information, especially for high involvement product categories, such as automobiles. Although Chinese differ from Europeans in terms of their online information search behavior, little research has been conducted in an effort to investigate patterns of online information search on Chinese populations. The goal of this study was to identify patterns of online information search and profile each pattern. Data were collected from automobiles consumers in Yinchuan, Ningxia Hui Autonomous Region, China. Three distinct search groups were identified. These three groups were profiled on a variety of demographic and socio-economic characteristics. This study highlights online information search behavior as a segmentation variable and provides meaningful implications for communication strategies directed to consumers in the third-tier cities in China.